Individually designed fully covered self-expandable metal stents for pediatric refractory benign esophageal strictures - Xing Wang (Nature Portfolio, 2021)
Abstract To share our institutional experience of placing individually designed fully covered self-expandable metal stents (FCSEMSs) for the treatment of refractory benign esophageal strictures (RBESs) in pediatric patients. A 10-year retrospective study between May 2009 and July 2020 that includes 14 children with RBESs who were treated with individually designed FCSEMSs. Patients were followed-up regularly after stent placement to observe the improvement of vomiting and dysphagia, changes in stenosis diameter and complications. A total of 20 stents were successfully placed in 14 patients. During a follow-up period ranging from 5 to 83 months, except for one 4-year-old child who could not endure chest pain, the remaining 13 patients all benefited from stenting. Their Ogilvie & Atkinson scores improved from grade III–IV to grade 0-I, and the diameters of the stenosis’ were enlarged from 2–5 mm to 9–14 mm. Two patients developed restenosis and granulation tissue hyperplasia was found in 2 patients and stent migration and malapposition in 2 patients with esophageal perforations that required further endoscopic intervention. The use of FCSEMS for RBES is safe and effective in selected pediatric patients. Rationally designed stents and timely management of postoperative complications are critical to ensure the success of this new method.